Physical appearance self-worth contingency as moderator of skin-tone surveillance consequences among university students in Polokwane - Majola, Matsobane Jeanette (My University, 2024)
Socially and culturally constructed skin tone-based notions of beauty reflect an extant Western gradation of physical beauty between peoples. The beliefs perpetuate biased attitudes and practices favouring fair skin. Consequently, skin-tone surveillance has become a norm among women in multicultural societies, each woman seeking to determine her station on the scale of beauty. Personal ways and means used by women who are pressured to constantly monitor their skin-tone are yet to be identified and clearly explained. This study investigated the moderator role of physical appearance contingent self-worth among female, black African university students in Limpopo, South Africa (N = 356). The students completed measures of skin-tone surveillance, physical appearance self-worth contingency, body modification behaviour and authentic happiness within a cross-sectional, correlational design. Correlation analysis found that authentic happiness was not related to any of the study variables. For that reason, it was excluded from the main analysis of the study. The results of moderation analysis show that the Appearance dimension of the Contingencies of Self-Worth do not act as moderator in the relationship between skin-tone surveillance and skin-related modification (bleaching) behaviour. The study results suggest that there is a need to further identify intervening factors that may ameliorate the burden of skin-tone monitoring
Thesis (M. A. (Clinical Psychology)) -- University of Limpopo, 2024
Keywords: Authentic happiness; Body modification behaviour; Moderation; Physical appearance self-worth contingency; Skin tone monitoring; Skin tone surveillance; Colorism; Skin; Self-esteem